The Place of the Issue in the Effectiveness of Historical Research - Seyed Abolfazl Razavi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
As the concern and ambiguity that a historian has extracted from the subject under study and attempts to explain and interpret it, this issue can be articulated in two ways: one aspect of the issue that is strongly intertwined with the subject and past time considerations is how the issue is realized. This aspect involves the disability and the process of realization of the issue and can be considerable in the light of the knowledge and expertise of the historian and other specialist historians in the age of study, but the causal aspect of the issue that deals with the cause of it is a category specifically associated with the subjective knowledge and ideas related to the considerations of the historian’s life and shows the status quo of the historian’s ecosystem whether in design or in response. The applied aspects of the knowledge of history and the interplay of past and present in the research of the historian, and the interdisciplinary nature of his research emerge in this aspect of the issue. This aspect, according to the historian’s past-oriented or modernist approach to the design, directs the reason for historical research. In this article, with a brief reflection on the status of the issue and the nature of its design, we examine the two approaches in explaining and designing the issue, and we reflect on their relevance to the effectiveness of historians’ research achievements.